2002
DOI: 10.1074/jbc.m112377200
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Calreticulin Modulates Protein Kinase B/Akt Signaling to Promote Apoptosis during Cardiac Differentiation of Cardiomyoblast H9c2 Cells

Abstract: Calreticulin is a Ca2؉ -binding molecular chaperone of the lumen of the endoplasmic reticulum. Calreticulin has been shown to be essential for cardiac and neural development in mice, but the mechanism by which it functions in cell differentiation is not fully understood. To examine the role of calreticulin in cardiac differentiation, the calreticulin gene was introduced into rat cardiomyoblast H9c2 cells, and the effect of calreticulin overexpression on cardiac differentiation was examined. Upon culture in a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
63
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 66 publications
10
63
2
Order By: Relevance
“…However, in human glioblastoma U251MG cells, overexpression of CRT-enhanced radiation-induced apoptosis by suppressing Akt signaling (Okunaga et al, 2006). Elevation of CRT promoted apoptosis during cardiac differentiation by negatively regulating Akt activation by upregulating the serine/threonine phosphatase PP2A (Kageyama et al, 2002). In mature cardiomyocytes, enhanced CRT expression disrupted intracellular calcium regulation, leading to calcium-dependent apoptosis (Lim et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in human glioblastoma U251MG cells, overexpression of CRT-enhanced radiation-induced apoptosis by suppressing Akt signaling (Okunaga et al, 2006). Elevation of CRT promoted apoptosis during cardiac differentiation by negatively regulating Akt activation by upregulating the serine/threonine phosphatase PP2A (Kageyama et al, 2002). In mature cardiomyocytes, enhanced CRT expression disrupted intracellular calcium regulation, leading to calcium-dependent apoptosis (Lim et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has shown that CRT protects fibroblasts from anoikis through binding to LRP1 and TSP-1 (Pallero et al, 2008). Akt activation or inactivation has been reported to play an important role in CRT-associated apoptosis (Kageyama et al, 2002;Okunaga et al, 2006;Lim et al, 2008). CRT-deficient mice show embryonic lethal characteristics due to changes in cell adhesiveness and impairment of cardiac development and function (Coppolino et al, 1997;Rauch et al, 2000;Mesaeli and Phillipson, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This is followed by receptor clustering and autophosphorylation and activation of JNKs (50). Recently, overexpression of calreticulin in myoblasts was associated with up-regulation of protein phosphatase 2A, further highlighting the potential for ER events to be transduced outside that compartment (51).…”
Section: Hsp47 Stimulates Collagen Productionmentioning
confidence: 99%
“…1995;Kageyama et al, 2002). It has been shown to be essential for cardiac and neural development in mice, but the mechanism by which it functions in cell differentiation is not fully understood.…”
Section: Antiangiogenic Factorsmentioning
confidence: 99%